Review of the uncertainties associated to hull girder hydroelastic response and wave load predictions. (May 2023) - Hirdaris, Spyros; Parunov, Josko; Qui, Wei; Iijima, Kazuhiro; Wang, Xueliang; Wang, Shan; Brizzolara, Stefano; Guedes Soares, C.
Abstract: This paper reviews the importance of uncertainties in hull girder loads influenced by flexible fluid structure interactions. The focus is on developments in the field of hydroelastic modelling, simulation and model tests of practical relevance to the prediction hull girder wave load predictions and their validation. It is concluded that whereas hydroelastic methods for use in design development and assessment become increasingly useful, challenges in realizing and modelling uncertainties can be attributed to: (1) the limitations of numerical methods to suitably model nonlinearities; (2) the ambiguity of model tests; and (3) the systematic use of data emerging from computational, model- or full-scale methods. An approach is recommended to assess the uncertainty in the hydroelastic responses to wave loading and an example is provided to demonstrate the application of the procedure. Highlights: Uncertainties in modelling and validation of wave loads is critical for ship design development and assessment. Hydroelasticity of ships is the preferred method for the assessment of ship springing, whipping and sloshing loads. Full scale measurements and model tests are essential means of validation. Uncertainty modelling should combine reliability theory and ISO GUM methods. Unified developments under ISSC and ITTC communities of practice presents the best way forward.